2014
DOI: 10.1007/s12663-014-0676-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparitive Evaluation of Propofol and Midazolam as Conscious Sedatives in Minor Oral Surgery

Abstract: Objective The objective of the study was to assess the efficacy of propofol and midazolam as an intravenous sedative agent in minor oral surgical procedures in terms of: (a) the onset of action, (b) heart rate, (c) oxygen saturation, (d) systolic and diastolic blood pressure, (e) respiratory rate, (f) pain during the injection of sedative agent, (g) recovery period, (h) side effects, (i) patient's cooperation during the surgery. Methodology This was a double blind randomized study in which one group of 20 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Midazolam increased the inhibitory effect of gamma-aminobutyric acid by binding between the alpha and gamma subunits present on the acid receptors [25]. Intravenous midazolam may cause respiratory depression due to direct suppression of the central respiratory drive, rather than as a result of simultaneous depression of the respiration muscles [26].…”
Section: Discussionmentioning
confidence: 99%
“…Midazolam increased the inhibitory effect of gamma-aminobutyric acid by binding between the alpha and gamma subunits present on the acid receptors [25]. Intravenous midazolam may cause respiratory depression due to direct suppression of the central respiratory drive, rather than as a result of simultaneous depression of the respiration muscles [26].…”
Section: Discussionmentioning
confidence: 99%
“…Propofol is a widely used intravenous anesthetic agent with rapid onset, short duration of action and rapid elimination (7). A number of pharmacological characteristics of propofol have been reported, including antipruritic, anti-convulsant, anti-oxidant and anti-inflammatory activities (8).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that propofol has a rapid on-rapid-off action with a short half-life of 20 minutes (Kotegawa et al, 2002). By contrast, midazolam have a longer duration of action compared to that of propofol, and a longer half-life of 49 min (Greenblatt et al, 2000;Hari Keerthy et al, 2015). In addition, the lower potency of propofol against PTZ kindled seizures could have been related to the rapid-on rapid-off action at GABAA receptors.…”
Section: Discussionmentioning
confidence: 99%